O caminho das pedras : cultura de uso de crack em Pernambuco - Almeida, Renata Barreto Fernandes de [UNIFESP] (2017)
In the last decades, drug use problems had became worrying, with serious consequences for the individual, his family and community, compromising the daily life of hundreds. Crack cocaine consumption emerged in Brazil in the late 1980's, and rapidly the phenomenon expanded and spreaded in whole country. Several researches point to a close relationship between the use of this drug and situations of vulnerability experienced by users. Considering the relevance of the issue, our work aimed to describe the culture of crack cocaine use in the State of Pernambuco, taking into account the set of knowledge, practices and worldviews shared by these users. For the development of this study we used a qualitative approach in which 39 semi-structured interviews of people over 18 years who used crack cocaine attended in the ATTITUDE Program – Comprehensive Care Program for Drug Users and their Families, managed by the Executive Secretary on Drug Policy of Pernambuco. It is an exploratory research on various aspects related to the culture of crack cocaine use. The analysis of the narrative data was performed based on the technique of content analysis, using the software NVivo v. 10.0. The results revealed the relationship between the social context in crack cocaine use and the increase of vulnerability situations experienced by these users. Several factors lead people to use the drug, but the curiosity and influence of friends were the most common. The interviewees described preference to use crack cocaine by oneself, in handmade pipes, without mixing of other drugs. The addiction on crack cocaine was observed in almost all the interviewees. Just few participants believed in the possibility of a controlled use of the drug. Compulsive use in binge pattern, and evolving with illicit or criminal acts to obtain the drug was recorded. Some criminal activities were informed to be realized on craving behavior to get fast financial return and to obtain the drug. Conflictive situations among users and imminent threats of death or imprisonment were observed in several reports. Finally, it is important to note that qualitative research related to crack consumption in Brazil is still scarce. Given the complexity of this problem, larger scientific investments need to be done to subsidize public policies on care and treatment turned to crack cocaine users attention to crack users.